A logic "OR" gate composed of a blue light‐induced CRISPR/dCas9 system and a Tet‐on system activates cancer suppressor genes to inhibit the growth of cutaneous squamous cell carcinoma cells. Issue 4 (6th October 2022) - Huang, Xinbo; Wang, Jieyi; Wu, Xia; Jiang, Bin; Chen, Menghui; Chen, Han; Mao, Yan; zhou, Cheng; Yu, Bo
Abstract: Optogenetic systems and tetracycline‐induced expression systems have been used in biological research. In gene circuits, light and tetracycline are often used to control the activation or inhibition of gene expression. In our study, we used a blue light induction system and tetracycline induction system to construct an "OR" logic gate, which can specifically induce the expression of p53 protein or E‐cadherin in the case of blue light or tetracycline, thus inhibiting the growth of cutaneous squamous cell carcinoma cells. Cutaneous squamous cell carcinoma is a kind of skin surface tumour. The activation of two tumour suppressor genes has a synergistic inhibitory effect on cutaneous squamous cell carcinoma, and blue light and tetracycline also provide a flexible means for gene regulation.